FAUNAL DIVERSITY AND ECOLOGICAL CHARACTERISTICS OF DENDROPHAGOUS BEETLES (COLEOPTERA) IN THE FERGANA REGION AND THEIR IMPACT ON FOREST ECOSYSTEMS - Asqaraliyeva, Sarvinoz (International Conference on Science, Education & Law, 2025)
The study examines the diversity, distribution, and ecological role of dendrophagous beetles (wood-feeding insects) in the Fergana region of Uzbekistan. A total of over 30 species from the families Scolytidae, Cerambycidae, Buprestidae, Scarabaeidae, and Curculionidae (order Coleoptera) were recorded. These beetles exhibit both beneficial and harmful ecological functions—participating in the decomposition of dead wood and nutrient cycling, while also causing significant damage to forestry and horticulture. The arid continental climate, extensive orchards, and irrigated plantations of Fergana Valley create favorable conditions for their reproduction. The study highlights the need for integrated pest management (IPM) strategies to mitigate the economic losses caused by these insects